Analysis and Forecasting of PT. Bank Rakyat Indonesia (BRI) Stock Price After Covid-19 using Multiple Linear Regression Method - Arief, M. Romli; Herlambang, Teguh (Universitas Islam Madura, 2025)
The Covid-19 pandemic that has occurred for approximately two years since 2020 in Indonesia has had a tremendous impact on the domestic economy. The impact is felt by many sectors, including the banking sector. In the banking sector, the economic downturn is also felt by investors, especially stock investors. Due to fluctuating stock price conditions, it also increases the number of uncertainties. This needs to be taken seriously by business people in the banking sector and investors so that companies are still able to operate in the midst of post-pandemic conditions. In times of crisis like today, investors, especially stock investors, have begun to adapt to the development of stock prices by taking an approach using advances in information technology. Updates from the field of information technology such as the use of machine learning with a technical approach or forecasting method have now begun to be utilized. This study aims to Analyze and forecast the closing price of shares of PT Bank Rakyat Indonesia Tbk using the Multiple Linear Regression method using reference stock data before and after covid-19 with a time span between 2018 and 2022. The forecasting results produced an RMSE value of 0.0256 in the condition of 90% training data and 10% test data.